PENGARUH PEMBERITAAN DI MEDIA SOSIAL TERHADAP TINGKAT KEPERCAYAAN KHALAYAK DI DESA LEUWILIANG KABUPATEN BOGOR - Wahdiyana , Fika (JURNAL SAHID DA'WATII, 2022)
In this era of modernization, almost all audiences use social media to communicate, the emergence of social media as new media makes it easier for audiences to access news on social media, not only to access news but people also use social media to share content. Content that is often disseminated on social media is one of the habits of today's audience. From social media, audiences can get information that is sometimes not necessarily true. In this study using a quantitative method with the title influence of news coverage on social media on the level of public trust with a total of 40 respondents, this research was conducted to examine and examine the extent to which the level of public trust in advertisements on social media. From this study, researchers obtained data that there was an effect of news on social media on the level of public trust, with 20.2% reporting on social media influencing the level of public trust.